Growth and Nutrient Uptake of Different Trees in Mine Spoils - Rao, A V; Tak, Richa (Annals of Arid Zone, 2016)
A pot experiment was conducted to compare the growth of different trees. their rhizosphere effect and nutrient uptake in gypsum and limestone mine spoils in relation to those of normal soil. Plant height and dry weight of shoots of different tree species were signiticantly reduced on an average by 44% and 36% respectively when g.own in gypsum and limestone mine spoils compared to those in normal soil. Gypsum mine spoils supported better growth than that of limestone mine spoils. Though the activities of various enzymes and the population of nitrifying bacteria were low in the rhizosphere of different plant species in both mine spoils, the rhizosphere effect was significantly high in mine spoils compared to that of normal soil. The population of Nitrosomonas in the rhizosphere of A. indica was less by 53% in gypsum mine spoils and 61% in limestone mine spoils. The root infection by AM-fungi and density of viable AMF spores varied among different plant species. Plants grown in gypsum and limestone mine spoils contained significantly lower concentrations of N, P. and Zn while the concentrations of Ca and Mg were significantly higher compared to those of normal soil indicating the deficiency/excess of different elements in these mine spoils. Introduction of different trees on mine spoils enhanced the development of active and diverse microbial community that help in stabilizing the mine spoils.